Sublimação, pulsão de morte, superego: o papel das teses freudianas sobre a cultura na elaboração das concepções metapsicológicas - Nakasu, Maria Vilela Pinto (Universidade Federal de São Carlos, 2009)
Considering that Freudian reflection about culture belongs entirely to the field of psychoanalytic investigation, as do neurosis or the facts of normal individual psychism, this work intends to verify how such reflection points out to the formulation and consolidation of metapsychologic notions. In order to do so, we will focus on sublimation, death pulsion and superego concepts, once they are crucial concepts of solidarity among these two reflections: metapsychology and theory of culture. In the same way, we aim at contributing to a more precise outlining of metapsychology meaning.
Keywords: Psicanálise; Freud, Sigmund, 1856-1939; Cultura; Metapsicologia; Sublimação; Pulsão de morte; Superego; Metapsychology; Theory of culture; Sublimation; Death pulsion; CIENCIAS HUMANAS::FILOSOFIA